2014
DOI: 10.2320/matertrans.m2014028
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Pit Initiation Process on Type 304 Stainless Steel

Abstract: In situ and real-time optical microscopic observations of pit initiation process on a commercial Type 304 stainless steel with low-sulfur content (0.004 mass%) were performed in 3 M NaCl solution at 298 K. MnS inclusions with diameters of ca. 1 µm were found to act as the initiation sites of pitting, as was the case in a re-sulfurized Type 304 stainless steel (0.027 mass%). The pit was initiated at the boundary between the MnS inclusion and the steel matrix, and grew with time. After a few seconds, no visible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…Chiba et al and Lillard et al demonstrated that a trench formed at the boundary of a MnS and steel matrix, was the initiation site of the pitting of stainless steels. 30,39,40 It is also known that the presence of MnS inclusions readily results in the pitting corrosion of carbon steels. 41,42 In this study, a small area without inclusions was selected as the electrode area during the microscale polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Chiba et al and Lillard et al demonstrated that a trench formed at the boundary of a MnS and steel matrix, was the initiation site of the pitting of stainless steels. 30,39,40 It is also known that the presence of MnS inclusions readily results in the pitting corrosion of carbon steels. 41,42 In this study, a small area without inclusions was selected as the electrode area during the microscale polarization.…”
Section: Resultsmentioning
confidence: 99%
“…However, the pit generation preceded the intergranular corrosion; therefore, the predominant factor is thought to be the existence of the inclusion at the grain boundaries. Chiba et al 18,19,29 proposed the pit initiation mechanisms at MnS inclusions in stainless steels. When MnS inclusions dissolve, the pH on and around the MnS is thought to decrease, 30,31 and is followed by the precipitation of elemental S. 19 In chloride solutions, the depassivation of the boundary between the inclusion and steel matrix occurs due to the synergistic effect of Cl − ions and elemental S. The trench is generated as selective dissolution at the boundary of the inclusions and steel matrix, and a pit is initiated inside the trench as a local transition from passive to active state.…”
Section: Effect Of Electrode Size On Pit Initiation-comparison Ofmentioning
confidence: 99%
“…Anodic polarization measurements of the specimens with an exposed area of around 1 cm 2 indicated an increase in the pitting corrosion potential of the carburized stainless steels with interstitial carbon compared to untreated stainless steels. 1,[3][4][5] The microscopic anodic polarization measurements of the carburized stainless steel with a micro-scale electrode area (around 150 μm × 300 μm) containing an MnS inclusion, which is known to act as an initiation site of the pitting of stainless steels, [10][11][12][13][14][15][16][17][18][19][20][21] demonstrated that no pitting was initiated on the carburized stainless steel despite the presence of the MnS inclusion. 6 The micro-scale electrode areas were in situ observed by an optical microscope with a water immersion objective lens (a lateral resolution of ca.…”
mentioning
confidence: 99%